2012
DOI: 10.1111/j.1365-294x.2012.05686.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical niche partitioning between cryptic sibling species of a cosmopolitan marine planktonic protist

Abstract: A large portion of the surface-ocean biomass is represented by microscopic unicellular plankton. These organisms are functionally and morphologically diverse, but it remains unclear how their diversity is generated. Species of marine microplankton are widely distributed because of passive transport and lack of barriers in the ocean. How does speciation occur in a system with a seemingly unlimited dispersal potential? Recent studies using planktonic foraminifera as a model showed that even among the cryptic gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 59 publications
(142 reference statements)
6
63
0
Order By: Relevance
“…These single-cell molecular studies have further revealed a detailed picture of the distribution patterns of the cryptic species of planktonic foraminifera, enabling comparison of the largely globally distributed morphospecies with the more restricted and ecologically specialized biogeography of their cryptic counterparts (e.g., de Vargas et al, 1999;Darling et al, 2007;Aurahs et al, 2009a;Morard et al, 2011;Seears et al, 2012;Weiner et al, 2012Weiner et al, , 2014. This approach provides a high resolution perspective for the construction of hypotheses on species dispersal, gene flow between populations and potential speciation mechanisms in the open ocean (de Vargas et al, 1999;Darling et al, 2000;Weiner et al, 2012Weiner et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These single-cell molecular studies have further revealed a detailed picture of the distribution patterns of the cryptic species of planktonic foraminifera, enabling comparison of the largely globally distributed morphospecies with the more restricted and ecologically specialized biogeography of their cryptic counterparts (e.g., de Vargas et al, 1999;Darling et al, 2007;Aurahs et al, 2009a;Morard et al, 2011;Seears et al, 2012;Weiner et al, 2012Weiner et al, , 2014. This approach provides a high resolution perspective for the construction of hypotheses on species dispersal, gene flow between populations and potential speciation mechanisms in the open ocean (de Vargas et al, 1999;Darling et al, 2000;Weiner et al, 2012Weiner et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Using the small subunit ribosomal RNA gene (SSU rDNA) as a marker, hidden genetic diversity was discovered within established morphospecies (Huber et al, 1997;de Vargas et al, 1999). This triggered a series of subsequent studies that screened morphospecies for their cryptic diversity (e.g., Darling et al, 1999;de Vargas et al, 1999;Aurahs et al, 2009a;Morard et al, 2009Morard et al, , 2011Weiner et al, 2012Weiner et al, , 2014André et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, biogeographical patterns based on morphospecies may be obscured by cryptic and polymorphic species, given that conserved, convergent or plastic morphologies can mask major molecular, biological, physiological and ecological differences (Dolan, 2015). The increasing combination of morphological and DNA sequence analyses in single specimens has revealed, for instance, cryptic species with different distributions and likely dissimilar ecology in marine plankton (Weiner et al, 2012;Ishitani et al, 2014;Santoferrara et al, 2015). Furthermore, the characterization of natural communities by high-throughput sequencing (HTS) is now offering the potential to reveal new distribution patterns based on the detection of rare species and the discovery of novel, atypical taxa that may not be recognized by microscopy, even in some groups with a long tradition of morphological description (Lecroq et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cryptic species can also arise in which genetically distinct species are morphologically indistinguishable (Weiner et al, 2012;Santoferrara et al, 2015). For some small protists, such as microchlorophytes, which can be difficult to identify due to their small size, high genetic diversity has been observed when morphotype characterization had suggested otherwise (Fawley et al, 2004) Conversely, in environmental samples, it can be difficult to assess whether genetic diversity has any morphological or physiological implications.…”
Section: Introductionmentioning
confidence: 99%